Edukasi Keluarga: Pencegahan Pneumonia pada Balita di RSUD Bayu Asih Purwakarta Tahun 2025 - Nengsih Yulianingsih; Ririn Riyani; Silvi Rahmasari Lestari; Malikah Fauziani; Silvia Rahma Wati; Imelda Eka Rosnia Wati; Sabilah Sabilah; Syifa Ayu Fitriana (PPNI UNIMMAN, 2025)
Pneumonia is a leading cause of morbidity and mortality in toddlers in Indonesia. Poor family knowledge about pneumonia prevention worsens children's health, necessitating educational efforts as a promotional and preventive measure. This community service activity aims to increase family knowledge and awareness regarding pneumonia prevention in toddlers through health education at Bayu Asih Regional Hospital, Purwakarta, in 2025. Implementation methods included lectures, interactive discussions, and the distribution of educational leaflets to 18 families of toddlers treated in the pediatric ward. Evaluation was conducted by comparing pretest and posttest results. The results showed an average increase in knowledge of 18%, from 76.7 to 90.3. Participants gained a better understanding of the risk factors, signs and symptoms of pneumonia, and preventive measures. Furthermore, families were more motivated to maintain environmental cleanliness, complete immunizations, and provide optimal nutrition for toddlers. In conclusion, family education is effective in increasing family understanding and awareness regarding pneumonia prevention in toddlers and can be a sustainable program in healthcare facilities.